2019
DOI: 10.1111/jdi.13067
|View full text |Cite
|
Sign up to set email alerts
|

Cancer has overtaken cardiovascular disease as the commonest cause of death in Scottish type 2 diabetes patients: A population‐based study (The Ayrshire Diabetes Follow‐up Cohort study)

Abstract: Aims/IntroductionThe increased mortality risk associated with diabetes is well established. The aim of the present study was to determine the causes of death of people with type 2 diabetes in Ayrshire and Arran, Scotland, between 2009 and 2014, and compare them with the national mortality rates.Materials and MethodsThe primary causes of death were collated. The causes of death were clustered into nine categories: heart disease, stroke, infection, renal failure, respiratory disorders, cancer, mental health, dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 33 publications
1
14
0
5
Order By: Relevance
“…T2DM appears to be an independent risk factor for pancreatic, endometrial, liver, colorectal, bladder and breast cancer [44]. Possible mechanisms linking diabetes with cancer include hyperglycemia and hyperinsulinemia (endogenous or exogenous), plus alterations of the insulin-like growth factor system, chronic subclinical inflammation, abnormalities in sex hormone metabolism, adipokines and possibly antidiabetes medication used in the management of T2DM [45].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…T2DM appears to be an independent risk factor for pancreatic, endometrial, liver, colorectal, bladder and breast cancer [44]. Possible mechanisms linking diabetes with cancer include hyperglycemia and hyperinsulinemia (endogenous or exogenous), plus alterations of the insulin-like growth factor system, chronic subclinical inflammation, abnormalities in sex hormone metabolism, adipokines and possibly antidiabetes medication used in the management of T2DM [45].…”
mentioning
confidence: 99%
“…A recently published population-based study [45] demonstrated that cancer has overtaken CVD as the commonest cause of death in T2DM patients in Scotland. Within the study period (2009-2014), 12.7% of people with T2DM died, the most common cause of death was cancer (27.8%), followed by heart disease (24.1%).…”
mentioning
confidence: 99%
“…Studies (Xu et al 2017;Yu et al 2018) have shown that an increase in insulin resistance and the incidence of hyperlipidemia has led to the global epidemic of T2DM. At present, the clinical treatment of T2DM centers more on good quality of life and extension of the lifespan of patients (Collier et al 2020). Drug therapy, diet, and exercise interventions are presently the mainstream treatments for T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-diabetes may be present approximately 5 to 15 years before diabetes is diagnosed and certain target organ impairmentsprimarily macrovascular complicationscan develop during this period (Ramlo-Halsted and Edelman, 1999). Moreover, the imbalance in carbohydrate metabolism creates favourable conditions for cancer development (Giovannucci et al, 2010;Nakamura et al, 2017;Collier et al, 2019). Epidemiological research has also confirmed that socio-economic status is a major factor in the development of pre-diabetes and T2DM (Vokó et al, 2009;Masseria et al, 2010;Kósa et al, 2011).…”
Section: Introductionmentioning
confidence: 95%